Cochlear synaptopathy - Encina-Llamas, Gerard (Auditio, 2024)
Our understanding of cell structure damage in the peripheral auditory system due to acoustic overexposure and ageing underwent a paradigm shift with the discovery, over a decade ago, of cochlear synaptopathy (CS) – the permanent loss of synaptic connections between inner hair cells and auditory nerve fibres. Until then it was upheld that hair cells, and outer hair cells in particular, were the most vulnerable element in the peripheral auditory system. The classical paradigm of clinical audiological assessment has always been - and still is - based on measuring hearing thresholds with pure-tone audiometry. However, the discovery of CS has made it more urgent to develop new and more accurate diagnostic methods to detect hearing damage that is hidden in audiometry and to develop more specific tests for different types of peripheral cell damage. This article reviews the scientific literature on CS in animal models and discusses the evidence of CS in humans from cadaveric studies. Finally, after giving an overview of various inconclusive studies using psychoacoustic and physiological techniques in living humans, the article outlines some of the work currently underway in some European universities and future prospects for diagnosing and treating peripheral hearing loss.